Determinants of Company Value with Environmental Performance as a Moderating - Sumampouw, Ruland Willy Jack; Putri, Nurhaliza (SAN Scientific, 2025)
The objective of the research is to examine the influence of leverage, liquidity, profitability, and institutional ownership on firm value with environmental performance as a moderating variable. The population in this study consists of coal sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 – 2023. The data analysis technique used in this study is panel data regression. The analysis results show that leverage does not affect firm value, liquidity negatively affects firm value, profitability positively affects firm value, institutional ownership does not affect firm value, environmental performance does not affect firm value, environmental performance cannot moderate the effect of leverage on firm value; environmental performance can moderate the effect of liquidity on firm value; environmental performance can moderate the effect of profitability on firm value. This study implies that companies need to focus on improving profitability and effective liquidity management while paying attention to environmental practices because environmental performance can strengthen the positive impact of profitability and reduce the negative impact of liquidity. For investors, environmental performance is an important consideration in assessing a company's ability to manage risk and create value.